Methodological and Theoretical Foundations of Family Values - Mamadiyarova Malika (Indonesian Journal Publisher, 2025)
In the current rapidly changing world, especially in rapidly developing social systems, man is constantly forced to adapt to new conditions. This leads to a revaluation of values. In the process of resolving conflicts and conflicts in social institutions, the system of values is also revised. Such flexibility and dynamic value system is necessary for a person’s personal growth and successful functioning in society. Values act as a beacon that guides a person not only in his inner world, but also in the external world